Trends in Academic Library Publications for the 2014-2023 Period in Scopus Database - Khaerani, Intan; Rahmi, Haifa Zulfani (Indonesian Journal of Librarianship, 2024)
Background:Every university has a library to support the academic community. The academic library does not only function to meet the informational needs of the academic community, but also plays crucial roles in education, research, information, recreation, and preservation. The importance of the academic libraries has led to numerous studies being conducted in this field. However, research developments in the field of academic libraries are not yet comprehensive due to the limited number of studies focused on its development. Purpose: The purpose of this research is to identify publication trends in the field of academic libraries within the Scopus database from 2014 to 2023 and to provide recommendations for research novelty in this field. Method: The research method used in this study is bibliometric analysis. The bibliometric method employed is co-word analysis (keywords) using VOSviewer software. Result: The trending keywords in publications on academic libraries from 2014 to 2023 included Academic libraries, Libraries, Information literacy, Library, Academic library, Human, Collection development, University libraries, Assessment, Higher education, Covid-19, Digital libraries, and Collaboration. Conclusion: The trending keywords in the field of academic libraries are related to the process of library’s adaptation to technological advancements, user needs, and the global impact of the pandemic. In addition to trending keywords, numerous less frequent keywords have emerged, including bibliometric analysis, digital skills, information literacy skills, digital collection, digital reference, digital repositories, technology transfer, technology adoption, remote access, information systems, library design, and academic library websites. These keywords offer valuable insights for future research in the field of academic libraries, particularly in the development of information technology in academic libraries so that libraries can continuously adapt to technological developments.